Relationship between the Leadership Style of the Head of the Health Center and Employee Involvement in Decision Making at the Selajambe Health Center: Fiki Sumanda, Lutiyah, Hendri Hadiyanto - Fiki Sumanda; Lutiyah; Hendri Hadiyanto (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Leadership is an important element and determines the smooth running of health services because leadership is the core of organizational management. Research using correlational analytics using a cross sectional approach emphasizes the time of measurement or observation of data on independent variables and dependent variables only once, at one time. The population in this study were 48 employees of the Selajambe Health Center. The sample used for research amounted to 43 people. The sampling technique used in this study was non-probability sampling. The data collection technique in this study was through interviews with the distribution of research instruments through questionnaires. The data analysis technique used is univariate analysis and bivariate analysis. The P Value obtained from the Chi Square test for asymp sig. (2-sided) is 0.000. This value shows the result of p <0.05 and means that Ha is accepted and H0 is rejected. So it can be concluded that there is a significant relationship between leadership style and employee involvement in making decisions at the Selajambe Health Center.